The Iodine/Iodide/Starch Supramolecular Complex - Szilard Pesek; Radu Silaghi-Dumitrescu (Molecules, 2024)
The nature of the blue color in the iodine–starch reaction (or, in most cases, iodine–iodide-starch reaction, i.e., I2 as well as I− are typically present) has for decades elicited debate. The intensity of the color suggests a clear charge-transfer nature of the band at ~600 nm, and there is consensus regarding the fact that the hydrophobic interior of the amylose helix is the location where iodine binds. Three types of possible sources of charge transfer have been proposed: (1) chains of neutral I2 molecules, (2) chains of poly-iodine anions (complicated by the complex speciation of the I2-I− mixture), or (3) mixtures of I2 molecules and iodide or polyiodide anions. An extended literature review of the topic is provided here. According to the most recent data, the best candidate for the “blue complex” is an I2-I5−-I2 unit, which is expected to occur in a repetitive manner inside the amylose helix.